INTERAKSI PERKEMBANGAN PSIKOLOGIS DAN LINGKUNGAN PEMBELAJARAN DALAM PEMBENTUKAN RASA PERCAYA DIRI PESERTA DIDIK SEKOLAH DASAR - Riska Cahya Arum Sari; Nadine Qothrunnada Dwihanti; Putri Ramadhani; Nadia Ayu Pramudita; Sulthan Ali Hakim; Surayanah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to analyze the interaction between psychological development and the learning environment in shaping the self-confidence of elementary school students. The study employs a qualitative approach with a descriptive design through a literature review. Research data were obtained from scientific literature sources consisting of national journals, scientific articles, and educational references relevant to psychological development, the learning environment, and the self-confidence of elementary school students. Data collection techniques were conducted through documentation and literature review based on criteria of topic relevance, year of publication, and source credibility. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that students’ psychological development, such as self-concept, motivation, emotional regulation, and social interaction skills, is closely related to the formation of self-confidence. Additionally, a positive learning environment plays a role in increasing students’ courage to participate in learning. The role of teachers, peer support, and the use of active and contextual learning strategies also contribute to building students’ self-confidence. Thus, the development of self-confidence in elementary school students is influenced by the interaction between internal and external factors that mutually support one another in the learning process. ABSTRAK Penelitian ini bertujuan untuk menganalisis interaksi perkembangan psikologis dan lingkungan pembelajaran dalam pembentukan rasa percaya diri peserta didik sekolah dasar. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif melalui studi literatur. Data penelitian diperoleh sumber literatur ilmiah yang terdiri atas jurnal nasional, artikel ilmiah, dan referensi pendidikan yang relevan dengan perkembangan psikologis, lingkungan pembelajaran, dan kepercayaan diri siswa sekolah dasar. Teknik pengumpulan data dilakukan melalui dokumentasi dan penelusuran literatur berdasarkan kriteria relevansi topik, tahun publikasi, serta kredibilitas sumber. Data dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perkembangan psikologis siswa, seperti konsep diri, motivasi, regulasi emosi, dan kemampuan interaksi sosial, memiliki hubungan erat dengan pembentukan rasa percaya diri. Selain itu, lingkungan pembelajaran yang positif turut berperan dalam meningkatkan keberanian siswa untuk berpartisipasi dalam pembelajaran. Peran guru, dukungan teman sebaya, serta penggunaan strategi pembelajaran aktif dan kontekstual juga berkontribusi dalam membangun rasa percaya diri peserta didik. Dengan demikian, pembentukan rasa percaya diri siswa sekolah dasar dipengaruhi oleh interaksi antara faktor internal dan faktor eksternal yang saling mendukung dalam proses pembelajaran.